Upaya meningkatkan hasil belajar siswa dengan menggunakan model kooperatif learning pada peserta didik kelas IV SDN 06 sitiung - Meri andani Padila rahayu,Peni Susmita (Jurnal Dharma PGSD, 2025)
Abstract: The background of the research is the use of cooperative learning models that are still rarely used by teachers, especially in mathematics learning on fraction material in gradeIV. Therefore, this study applies a cooperative learning model to determine the improvement of student learning outcomes. The use of the cooperative learning model provides opportunities for students to express their thoughts in small groups. The research method used is classroom action research (CAR) to analyze learning outcomes from the pre-cycle and then apply treatment using the cooperative learning model. In the first cycle, the number of students with scores below the average was 11 students with an average class score of 68, while in cycle 2, students who got scores below the average were 8 students with an average class score of 75. The number of students who got scores above the average was in cycle 1 as many as 15 students while in cycle 2 as many as 18 students. These data indicate an increase in student learning outcomes at SDN 06 Sitiung.